Control strategies for charging and discharging policies of rechargeable batteries - Dong, Ye (2013)
The rechargeable batteries will play a more and more important role in the future. This is because they can make a great contribution to many areas. Like for example the efficiency of the performance, the need for energy conservation, environment protection and so on. As a result, Li-ion battery will finally become a leading candidate for the next generation rechargeable batteries. However, there are still some difficulties in making full use of Li-ion battery. This report is focused on the challenge of the control strategies for charging and discharging policies of Li-ion battery.